2008
DOI: 10.1359/jbmr.080304
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Osteogenic Differentiation Potential of Mouse Bone Marrow Stromal Cells

Abstract: Age-dependent bone loss has been well documented in both human and animal models. Although the underlying causal mechanisms are probably multifactorial, it has been hypothesized that alterations in progenitor cell number or function are important. Little is known regarding the properties of bone marrow stromal cells (BMSCs) or bone progenitor cells during the aging process, so the question of whether aging alters BMSC/progenitor osteogenic differentiation remains unanswered. In this study, we examined agedepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 48 publications
(85 reference statements)
6
93
0
3
Order By: Relevance
“…We also found that osteoclast colonies are markedly increased in bone marrow cultures from aged mice, especially when they are induced toward adipogenic differentiation, and that they survived for several months. Although it is generally recognized that osteoblastogenesis decreases with aging, it has also been reported that CFU-F increases and CFU-Ob remains unaltered or even increases until 18 months old in mice (40,41), implying that differences in culture conditions and the sex and age of animals used are important.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that osteoclast colonies are markedly increased in bone marrow cultures from aged mice, especially when they are induced toward adipogenic differentiation, and that they survived for several months. Although it is generally recognized that osteoblastogenesis decreases with aging, it has also been reported that CFU-F increases and CFU-Ob remains unaltered or even increases until 18 months old in mice (40,41), implying that differences in culture conditions and the sex and age of animals used are important.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation process, negative immunodepletion (CD11b, CD45R/B220, CD11c, plasmacytoid dendritic cell antigen-1 [PDCA-1]), positive immunoselection (stem cell antigen-1 [Sca-1]), and retroviral infection (GFP) have been described previously. 28,29 First, six mice per age group were euthanized by CO 2 overdose followed by thoracotomy. The femora and tibiae were dissected free of soft tissues and kept in cold PBS on ice.…”
Section: Isolation and Culture Of Bmscsmentioning
confidence: 99%
“…Resulting CD11b, CD45R/B220, CD11c, PDCA-1-negative cells were subjected to positive immunoselection using antiSca-1 microbeads (Miltenyi Biotec) following the manufacturer's recommendations. Enriched BMSCs (3 months: 1.35% CD45, 1.45% CD11b, 74.46% Sca-1; 18 months: 0.33% CD45, 0.13% CD11b, 83.18% Sca-1 by FACS analysis 28 ), which are depleted of monocytes, granulocytes, macrophages, myeloid-derived dendritic cells (DCs), natural killer cells, B-1 cells, B lymphocytes, T lymphocytes, classical DCs, plasmacytoid DCs, and macrophage progenitors, were maintained in the Dulbecco's modified Eagle's medium (DMEM; Cellgro) with 10% heat-inactivated FBS (Atlanta Biologicals), and shown of possessing multilineage potential. 28 Of note, BMSCs derived from 3-month-old animals at this stage were used for comparisons with whole BM cell isolates (see above) derived from a second set of 3-monthold mice.…”
Section: Isolation and Culture Of Bmscsmentioning
confidence: 99%
“…Esse resultado foi semelhante ao observado por outros estudos (11)(12)(13)(14)(15)17,18). Segundo Hell e cols.…”
Section: Discussionunclassified
“…Contudo, tanto em animais quanto em seres humanos a diferenciação osteogĂȘnica das CTM-MO pode ser comprometida pela idade ou por doenças como a osteoporose e as disfunçÔes tireoidianas, entre outras (11)(12)(13)(14)(15)(16)(17)(18). Assim, o efeito da idade poderia limitar o uso da terapia com cĂ©lulas-tronco autĂłlogas em pacientes adultos ou idosos.…”
Section: Introductionunclassified